Changes in attentional resources during the acquisition of laparoscopic surgical skills. Issue 2 (23rd December 2020) - Thomaschewski, M; Heldmann, M; Uter, J C; Varbelow, D; Münte, T F; Keck, T
Abstract: Background: Increasing familiarity and practice might free up mental resources during laparoscopic surgical skills training. The aim of the study was to track changes in mental resource allocation during acquisition of laparoscopic surgical skills. Methods: Medical students with no previous experience in laparoscopic surgery took part in a 5-week laparoscopic training curriculum. At the beginning and end of the training period, one of the training tasks was combined with a secondary auditory detection task that required pressing a foot switch for defined target tones, creating a dual-task situation. During execution of the two concurrent tasks, continuous electroencephalographic measurements were made, with special attention to the P300 component, an index of mental resources. Accuracy and reaction times of the secondary task were determined. Results: All 14 participants successfully completed the training curriculum. Target times for successful completion of individual tasks decreased significantly during training sessions ( P <0.001 for all tasks). Comparing results before and after training showed a significant decrease in event-related brain potential amplitude at the parietal electrode cluster (P300 component, W = 67, P = 0.026), but there were no differences in accuracy (percentage correct responses: W = 48, P = 0.518) or reaction times (W = 42, P = 0.850) in the auditory detection task. Conclusion: The P300 decrease in the secondary task over training demonstrated a shift of mental resources to the primary task: the surgical exercise. This indicates that, with more practice, mental resources are freed up for additional tasks.